Possibilities of Transportation System Management through Market Activities - Teodor Perić; Željko Radačić (Promet - Traffic&Transportation, 1970)
In the whole cycle of production, distribution, exchangeand coi!Sumption, the market is the place of exchange andrealisation of the manufactured products and services. Marketis the main f01m of link between the producer and the consumer;it is on the market that supply and demand are balanced,the two basic market categories.Because of the specific characteristics of the transp011ationprocess, the economic theory coi!Siders that there is no uniquemarket of traffic services, but rather that there are lransp011alionmarkets on ce11ain relations. Thus, one can speak of theimpe!feclion of the transportation market and its impossibilityto balance traffic supply and demand due to unity of supply anddemand, due to non-flexibility of traffic supply regarding trafficdemand, due to technical characteristics of traffic infrastructure,and due to various technical and technological characteristicsof cenain transponation branches. Therefore, the relationsbetween supply and demand cannot be regulated automaticallyby transporlation market, and consequently, neithercan the structuring of the transp01tation system rely only on theinfluence of the transp01tation market. This is why govemmentappears as the CO!Tective measure of the market, i.e. governmentregulation of supply and demand. This govenzment regulationis realised through general economic and transportationpolicy.